Peru - Selected Issues in Fiscal Policy : Taxation and Equity - Junquera-Varela, Raul Felix; Vostroknutova, Ekaterina (World Bank, Washington, DC, 2021)
This report takes an in-depth look, from a policy perspective, at the trade-offs between increasing tax collection and improving the equity of the fiscal system. As part of this effort, the report places the Peruvian tax system in an international context and considers the key challenges the government is facing in its drive to increase revenue. It also conducts qualitative and quantitative analyses of the impact of taxes and transfers on inequality and on the distribution of income. The report then makes several policy proposals that would increase tax collection without jeopardizing equity, and it then simulates the impacts of these changes on collection and equity. This advice spanned the 2012-2014 period, and included research on several tax policy-related issues, such as legal advice on double-taxation treaties and in-depth analyses of tax exemptions. To keep the focus tight, some of the work is not included in this report. Contributions were originally written in Spanish to provide the Ministry of Economy and Finance (MEF) with timely advice on the subject and were discussed with the counterparts during and immediately after its preparation. As a result of prioritizing this process, two teams focused on different areas of research and were able to contribute to the analytical base behind the ongoing tax reform. The report summarizes the main elements of this process and resulting advice. It comes out at the same time as the finance ministry announces the first set of tax reforms that were informed by this work.